A modified reference strain method for engineering critical assessment of reeled pipelines. (January 2016) - Jia, Pengyu; Jing, Hongyang; Xu, Lianyong; Han, Yongdian; zhao, Lei
Abstract: Reel-lay is a highly efficient method employed to install small or medium diameter offshore pipelines that play a key role in transportation of crude oil and natural gas. However, pipelines are subjected to 1–3% plastic straining during the process of reel-lay; thus engineering critical assessment (ECA) must be carried out to obtain the crack-like defect acceptance criteria. In our work, the effects of pipe geometry, crack geometries, and material properties on the reference strain are investigated. Furthermore, an empirical formula is proposed to estimate the reference strain. By incorporating the reference strain, the application range of the strain-based failure assessment diagram method is extended to ECA of severe circumferential surface cracks in reeled pipes. Highlights: An empirical formula for the reference strain is proposed. The formula extends the application of the SB-FAD method to reeled pipes. The modified reference strain method is verified to be valid.